Conflicted health care : professionalism and caring in an urban hospital - Apesoa-Varano, Ester Carolina, 1975-; Varano, Charles S., 1957- (Vanderbilt University Press, 2014)
"This book takes an intimate look at how health care practitioners struggle to live up to their professional and caring ideals on twelve-hour shifts on the hospital floor"--Provided by publisher